Metodologia detalhada para rastreadores solares automatizados de dois eixos em sistemas fotovoltaicos - Ramos, Lucas Feksa (2016)
The search for diversity of energy sources in the world is one of the challenges that are driving research to fill this demand with alternative energy sources. So we have the need to explore alternative and renewable resources that bring flexibility and sustainability in its use. Presented before the panorama, the generation of electricity with solar photovoltaic systems is a trend, and has its technology constantly advancing, presenting itself as an immediate solution to this pursuit of diversity. The energy extracted from the Sun in photovoltaic generation systems depends on the flow of energy from the solar radiation in a plane perpendicular to the rays. Therefore, the average solar energy obtained by conventional solar panels during the course of the day, is not always maximized. One reason is that the fixed panels are not at an angle of zero degree zenith in relation to the Sun position. Thus, the movement East (E) to the West (W) daily, with the Earth's seasonal, directly affects the radiation intensity received by the photovoltaic panels. In this context, solar trackers can be used as devices that improve substantially the efficiency of photovoltaic panels, by letting them always perpendicular to the incident radiation received from the sun. In this dissertation demonstrates a methodology for automated solar tracking two axes for photovoltaic panels. The qualitative and quantitative results presented here show the real gain in power generation through the development of a real-time control algorithm for solar tracking systems of two axes, with their simulations and testing a low-cost prototype, developed in laboratory Center of Excellence in Energy and Power Systems (CEESP). Moreover, the results show that this methodology adapts successfully to the different conditions of use to track the sun's position, both in the laboratory and in the field.